Photodouble ionization of water studied by photoelectron–photoelectron coincidence experiments. (14th March 2019) - Turri, G; Bolognesi, P; Sugimoto, H; Mathis, J; Avaldi, L
Abstract: The photodouble ionization of the water molecule has been studied at about 20 eV excess energy by detecting in coincidence two photoelectrons of equal energy. Two types of measurements have been performed. In the first one the photon energy has been scanned in order to reconstruct the spectrum of the H2 O 2+ states; in the second, the photon energy has been fixed, the direction of one photoelectron has been chosen along the direction of the polarization axis of the incident radiation and the coincidence angular distribution of the two photoelectrons has been measured. The angular distributions show that, at variance with previous measurements in diatomic molecules, the emission of the two electrons along the antiparallel direction is highly favored.